Поздовжня спінова динаміка у гайзенбергівському антиферомагнетику: двомагнонні збудження - Boliasova, O. O.; Krivoruchko, V. N. (Publishing house "Academperiodika", 2020)
Understanding the ultrafast spin dynamics in magnetically ordered materials is important for the comprehenssion of fundamental limits in spin-based magnetic electronics – magnonics. We have studied a microscopic model of magnetization dynamics in a two-sublattice antiferromagnet with the emphasis on longitudinal spin excitations. The diagrammatic technique for spin operators has been used to overcome limitations typical of phenomenological approaches. The graphical representations of spin wave propagators allow us to summing up the infinite series of distinctive diagrams. Its sum is transformed into an analytic expression for the longitudinal spin susceptibility xzz (q, w) applicable in all regions of the frequency w and wave vector q spaces beyond the hydrodynamical and critical regimes. It is found that the longitudinal magnetization dynamics consists of two types of excitations, which have different dependences on the temperature and wave vector q. The obtained result could be important for understanding the physics of nonequilibrium magnetic dynamics under the effect of ultrafast laser pulses in antiferromagnetic materials.